Swaps and Roosa Bonds as an Index of The Cost of Cooperation in the "Crisis Zone" - Makin, John H. (Quarterly Journal of Economics, 1971)
I. Introduction, 349. — II. Swaps and Roosa Bonds as substitutes for conversion of dollars into gold, 349. — III. A portfolio behavior model for reserve assets, 351. — IV. Empirical results, 353. — V. Summary and conclusions, 355. — Appendix, 355.